IMPLEMENTASI STUDY TOUR DENGAN PENDEKATAN MEANINGFUL LEARNING PADA MATERI DAERAH KEBANGGAANKU UNTUK SISWA KELAS V SD - Rusandiansyah, Muhammad Nifan; Yasir Arafat; Murjainah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is a descriptive qualitative research. The purpose of this study was to describe the implementation of a study tour using the Meaningful Learning approach in the "My Proud Region" material for fifth-grade students of SD Negeri 230 Palembang. This research was motivated by the implementation of study tours that still tended to be recreational and had not been optimally integrated with learning objectives, resulting in students' learning experiences not being fully meaningful. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. Data analysis techniques used data reduction, data presentation, and data verification, while data validity was ensured through source, technique, and time triangulation. The results showed that the implementation of the study tour using the Meaningful Learning approach was carried out very well through the stages of planning, implementation, and learning evaluation, achieving 90% in the observation assessment (Very Good category) and 95% in the student questionnaire (Very Good category). The implementation of the study tour with the Meaningful Learning approach was effective in creating contextual, meaningful, and enjoyable learning and was able to improve students’ conceptual understanding and sense of pride toward regional culture.